The heretical pedagogy of los olvidados - Fernández, Olivia (2017)
The aim of this text is to analyse the subversive pedagogical value of this work, directed by Luis Buñuel in Mexico, 1950, as shown in the oneiric sequence of the dream, which has been highlighted in different context as one of the most important characteristics of the Buñuelian cinema, giving him a unique place in the history of cinematographic creation. This value has not only a paradigmatic dimension (which is comparable with those of Griffith, Eisenstein, John Ford, Hitchcock, Bergman and Godard), but, in fact, it implies another most important pedagogical dimension as a source of subversion of the reading and apropriation mechanisms that the spectators have been acquiring along with their film and cinematographic cultures - which means, in fact, their film literacy. In this text we will analyse the symbolic and the intertextual dimensions that give the character of obvious surreal content to the oneiric film excerpt in LOS OLVIDADOS - a film text within a film text - comparing the Buñuelian film indications with the final result of the filmed audiovisual sequence.